The association between personality, coping and depressive symptoms in adult patients with chronic pain - Deif, Reem Mohamed Ahmed (AUC Knowledge Fountain, 2018)
As a rising concern in the medical and mental health fields, this study aims to examine predictors of depressive symptoms in a sample of Egyptian chronic pain patients in terms of coping styles and personality traits. Patients with chronic pain are believed to experience different stressors which include, but are not limited to, pain, disability, reduced productivity and financial difficulties. Such factors, in addition to various psychosocial factors, constitute the disease burden of chronic pain. This study examines the degree to which coping styles and personality traits can influence the disease outcome in terms of comorbid depressive symptoms. A total of 98 (50 patients with fibromyalgia and 48 patients with rheumatoid arthritis) patients were interviewed and were assessed in terms of their coping styles, personality profile and severity of depressive symptoms. Results show a high prevalence of depressive symptoms and suggest passive coping, high neuroticism, low extraversion, unmarried status and more years of education. to be moderate predictors of the severity of chronic pain. Findings of this study shed light on the significance of the psychological aspects of chronic pain conditions and may help in designing liaison interventions for the management of secondary and comorbid depressive symptoms.